1972
DOI: 10.1128/aac.2.3.103
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Resistance and Collateral Susceptibility to Antifolic Antimalarial Compounds

Abstract: Series of strains of Streptococcus faecium ATCC 8043, Lactobacillus casei ATCC 7469, and Pediococcus cerevisiae ATCC 8081 with increasing resistance to the active antifolate antimalarial drugs chlorguanide triazine (CGT), pyrimethamine (PM), and trimethoprim (TMP) were isolated. These mutant strains, stable for at least 3 to 5 years, were examined for cross-resistance and collateral susceptibility to the above compounds and to methotrexate (MTX). Generally, they exhibited crossresistance to all four compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
1981
1981

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…These TMP-resistant V. anguillarum strains were also insensitive to the vibriostat 0/129 (Table 2). This cross-resistance suggests that the drugs are related compounds (Smith & Genther 1972). Muroga, Yoneyama & Jo (1979) have also reported the isolation of V. anguillarum strains insensitive to 0/129 and suggested that the strains were cross-resistant to trimethoprim and sulphadoxine (formerly sulphormethoxine; 4-p-aminobenzenesulphon amido-5,6-dimethyloxyprimidine).…”
Section: Discussionmentioning
confidence: 99%
“…These TMP-resistant V. anguillarum strains were also insensitive to the vibriostat 0/129 (Table 2). This cross-resistance suggests that the drugs are related compounds (Smith & Genther 1972). Muroga, Yoneyama & Jo (1979) have also reported the isolation of V. anguillarum strains insensitive to 0/129 and suggested that the strains were cross-resistant to trimethoprim and sulphadoxine (formerly sulphormethoxine; 4-p-aminobenzenesulphon amido-5,6-dimethyloxyprimidine).…”
Section: Discussionmentioning
confidence: 99%